Herramienta web para la gestión de inventario, usuarios, matrículas y mensualidades para el gimnasio gym platinum del municipio de Quimbaya Quindío (2020)
The GYM PLATINUM gym is a recreation and sports company, located in the municipality of Quimbaya Quindío, which offers collective training classes personalized physique and sports supplements. This company had several shortcomings in the collection of registration documentation and monthly payments (lost documents and difficulties in the search for information) causing delays in weather. In addition, it did not have a record of the activities carried out by the trainers and muscle measurements of clients. It also featured problems in the stock of products and inventory of machines since it did not carry a registry. The main objective of this project was to develop a web tool for the management of users, inventory, registrations and monthly payments for the GYM PLATINUM gym. Responsive design technology was used in the web tool, to adapt to the size of different types of devices and was accessible from a web browser. This project is part of the internship that ran for 4 months and used the prototyping methodology evolutionary for software development.